Penilaian Keterampilan Proses Sains Pada Praktikum Mahasiswa di Laboratorium Kimia - Kriswantoro, Kriswantoro; Wulandari, Lucya; Sainuddin, Syamsir; A.J, Suharli (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Science process skills (SPS) are essential competencies that students must possess during laboratory activities to support conceptual understanding and the development of scientific thinking abilities. This study aims to assess the level of students' mastery of SPS and evaluate the effectiveness of chemistry practicum activities in enhancing these skills. The research employs a quantitative approach with a descriptive-evaluative design. The subjects are second-semester students participating in a basic chemistry practicum. The SPS assessment instrument, consisting of 18 items, was developed and validated, yielding an average Aiken’s V index of 0.84, indicating high validity. The results show that most students demonstrated strong skills in observation (76%) and classification (68%), but showed weaknesses in higher-order skills such as formulating hypotheses (35%), designing experiments (30%), and understanding experimental variables (25%). Skills in data interpretation (45%) and oral scientific communication (40%) also require improvement. These findings highlight the need to strengthen inquiry-based learning and consistently apply process-oriented assessment in chemistry practicum activities to comprehensively develop students’ science process skills.